Spatial variability of the least limiting water range of soils under a no‑tillage system - Klein, Vilson Antonio; Graebin, Gilvan Jaciel; Bortolanza, Delcio Rudinei; Daubermann, André Guilherme (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the regressions that define the least limiting water range limits and the validity of using this indicator considering the spatial variability of crops under a no‑tillage system. One hundred undisturbed soil samples were collected in areas with dimensions of 10x10 m, in two different Oxisols and an Ultisol managed under no‑tillage. Air‑filled porosity (0.10 m3 m-3), field capacity (potential of ‑ 0.006 MPa), permanent wilting point (potential of ‑ 1.5 MPa), and soil mechanical resistance (2 MPa) were determined. The regressions that described field capacity had the lowest coefficients of determination, whereas those that described air‑filled porosity, permanent wilting point, and soil mechanical resistance to penetration showed the highest values. Regression adjustments that define field capacity limits are not accurate in explaining variation on volumetric soil water content through bulk density, and the evaluated soils show high spatial variability regarding the least limiting water range.